The right of access to educational materials and copyright: international and domestic law - Samtani, S (2021)
International rules regulating copyright pose obstacles to accessing educational materials, particularly impacting persons living in poverty, persons living with disabilities and other marginalised groups. This Thesis argues that access to educational materials is a human right under the right to education and imposes obligations upon states. State obligations under human rights law thus appear to conflict with international copyright obligations for common parties. In demonstrating that states can reconcile these competing obligations harmoniously, the Thesis advances a rights-based response to the problem of access for those neglected by the market.